O16.6 Pre-Vaccination Seroprevalence of 15 Human Papillomavirus (HPV) Types Among Slovenian Women Screened For Cervical Cancer. (13th July 2013) - Klavs, I; Učakar, V; Jelen, M M; Faust, H; Dillner, J; Poljak, M
Abstract : Background: Our objective was to estimate the seroprevalence of 11 high-risk (hr) HPV types (HPV 16, 18, 31, 33, 35, 39, 45, 52, 56, 58, 59) and four low-risk (lr) HPV types (HPV 6, 11, 68, 73) among Slovenian women screened for cervical cancer before the introduction of vaccination against HPV. Methods: 3259 serum specimens from the Slovenian HPV prevalence survey were tested for HPV type-specific antibodies with a multiplexed pseudovirion-based serological assay (PsV-Luminex). Results: Seropositivity for any of the 15 HPV types was 65.7%, any of the 11 hr-HPV types 59.2%, and any of the four lr-HPV types 33.1%. Antibodies against multiple HPV types were more common (45.3%) than against single HPV types (20.4%). Antibodies against at least one of the four vaccine HPV types (HPV 6, 11, 16, and 18) were detected in 40.8% women. Among hr-HPV types seropositivity was the highest for HPV 16 (25.2%) and among lr-HPV types for HPV 6 (19.1%). Age-specific seropositivity for HPV 16 was the highest among 30–39 years old women (29.6%) and decreased with increasing age to 14.0% among 60–64 years old women (p = 0.014). Seropositivity for any of the hr-HPV among women with pathological cytology was 76.8% and those negative for intraepithelial lesion or malignancy 58.3% (p < 0.001). Conclusion: Our results show a substantial burden of lifetime sexual exposure to these 15 HPV types before the introduction of vaccination and also a relatively high cumulative exposure to at least one of the four vaccine HPV types. Thus, vaccination of females before sexual debut with a quadrivalent HPV vaccine has a potential to contribute to a substantial reduction of the burden of cervical infections and cervical cancer as well as some other HPV related morbidity, including genital warts. Our data also present the baseline for monitoring HPV long-term vaccination impact.